Lineariza??o adaptativa por alimenta??o direta de amplificadores de pot?ncia empregando FPGA - Pereira, Orlando dos Reis (2007)
This dissertation presented the implementation in FPGA of a feeddorward amplifier for two sinusoidal input signals in 7 MHz. The blocks were developped with Simulink, using Xilinx System Generator blocks. The optimization software implemented in VHDL is an adaptation of the original Hooke and Jeeves algorithm. The error loop results approximated very well the expected data, proving the efficiency of our adaptative system.